National Deadlock. Hot Nationalism, Dual Identities and Catalan Independence (2008–2019) - Alejandro Quiroga; Fernando Molina (Genealogy, 2020)
The article explores the transformations of Spanish and Catalan national identities and the growth of the pro-independence movement in Catalonia following the 2008 global recession. It argues that the Great Recession provided a new historical context of hot nationalism in which Catalanist narratives of loss and resistance began to ring true to large sectors of Catalan society, whereas the Spanish constitutionalist narratives seemed increasingly outdated. The article also shows the limits of the process of mass nationalization by both the Catalan and the Spanish governments and the eventual 'crystallization' of an identity and political divide between pro and anti-independence supporters which split Catalan society down the middle and led to a sort of national identity deadlock.